Ocean counting - Lawler, Janet (National geographic little kids., 2013)
Presents young readers with a foundation for learning basic counting skills while discovering some magnificent ocean animals. Fact boxes in the back of the book include information about the animals' homes, sizes, diets, predators, and babies.